Image compression and decompression techniques for future application in transmission to remote monitoring center using telephone network: software development / Alwi Hasrat - Hasrat, Alwi (1995)
This thesis proposes a software development of image data compression and decompression techniques. The compression takes place through a process of removal redundant data in image file and representing the data to more efficient codes. After completing the compression process, the amount of data required to represent digital image is reduced. This reduction is justified from compression ratio. Whereas, decompression is done through inversion of compression to get the original amount of data for that particular image file. Both techniques can be performed by using LZW and Huffman algorithm. For future application, the compressed image file is to be used in image transmission over telephone network via modem to remote monitoring center. The software development is done using Turbo C++ language in the DOS environment.